Tyrosine kinase mutations in gastrointestinal stromal tumors in a nation-wide study in Iceland. - Tryggvason, G; Hilmarsdottir, B; Gunnarsson, G H; Jonsson, J J; Jonasson, J G; Magnusson, M K (APMIS, 2010)
To access publisher full text version of this article. Please click on the hyperlink in Additional Links field Gastrointestinal stromal tumor (GIST) is the most common mesenchymal tumor of the gastrointestinal tract. It is characterized by activating mutations in the tyrosine kinase genes c-kit or PDGFRA. This study examined the mutation rate and type in a population-based material. All gastrointestinal mesenchymal tumors over the years 1990-2004 were evaluated and GIST tumors identified using immunohistochemistry (c-kit) and conventional pathologic parameters. Paraffin sections from all tumors were subjected to mutation analysis on exons 9, 11, 13 and 17 of the c-kit gene and exons 12 and 18 of the PDGFRA gene. To screen for mutations, we used a highly sensitive conformation-sensitive gel electrophoresis (CSGE) and to define the mutated alleles, we employed direct automated DNA sequencing. All c-kit-positive gastrointestinal mesenchymal tumors were entered into the study. Fifty-six tumors from 55 patients were analyzed. Mutations were found in 52 tumors representing a 92.9% mutational rate. Most of the mutations were found in c-kit exon 11 (76.8%), followed by c-kit exon 9 (10.7%). PDGFRA mutations were only found in three tumors. No correlation of mutation type with biologic behavior was found. This population-based study, using a sensitive CSGE method, identifies mutations in the great majority of patients with GIST.